2015
DOI: 10.1093/nar/gkv239
|View full text |Cite
|
Sign up to set email alerts
|

Mycoreovirus genome rearrangements associated with RNA silencing deficiency

Abstract: Mycoreovirus 1 (MyRV1) has 11 double-stranded RNA genome segments (S1 to S11) and confers hypovirulence to the chestnut blight fungus, Cryphonectria parasitica. MyRV1 genome rearrangements are frequently generated by a multifunctional protein, p29, encoded by a positive-strand RNA virus, Cryphonectria hypovirus 1. One of its functional roles is RNA silencing suppression. Here, we explored a possible link between MyRV1 genome rearrangements and the host RNA silencing pathway using wild-type (WT) and mutant stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 66 publications
0
34
0
Order By: Relevance
“…Various interactions have been reported in the C. parasitica/virus system: one-way synergism between CHV1 [nonsegmented (+) RNA genome] and MyRV1 (11-segmented dsRNA genome) (36), and the generation of MyRV1 genome rearrangements by CHV1 coinfection; transgenic expression of its RSS, p29; or deletion of host dcl2 or agl2 (37,38). This study focused on different virus/ virus interplays involving RnVV1 (undivided dsRNA genome) and showed that (i) MyRV1 and an RSS-lacking CHV1 mutant, CHV1-Δp69, interfere with the replication and lateral transmission of unrelated RnVV1 in WT C. parasitica; (ii) this interference is also mediated by transgene-derived dsRNA; (iii) disruption of dcl2 completely abolished the interference, whereas disruption of agl2 did not always do so; and (iv) the interference coincided with high levels of accumulation of the dcl2 and agl2 transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Various interactions have been reported in the C. parasitica/virus system: one-way synergism between CHV1 [nonsegmented (+) RNA genome] and MyRV1 (11-segmented dsRNA genome) (36), and the generation of MyRV1 genome rearrangements by CHV1 coinfection; transgenic expression of its RSS, p29; or deletion of host dcl2 or agl2 (37,38). This study focused on different virus/ virus interplays involving RnVV1 (undivided dsRNA genome) and showed that (i) MyRV1 and an RSS-lacking CHV1 mutant, CHV1-Δp69, interfere with the replication and lateral transmission of unrelated RnVV1 in WT C. parasitica; (ii) this interference is also mediated by transgene-derived dsRNA; (iii) disruption of dcl2 completely abolished the interference, whereas disruption of agl2 did not always do so; and (iv) the interference coincided with high levels of accumulation of the dcl2 and agl2 transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Total nucleic acids were extracted from the mycelia of fungal strains cultured in 20 ml PDB and dsRNA fractions were isolated as described by (Eusebio‐Cope and Suzuki, ). All strains were cultured on PDA overlaid with cellophane (PDA‐cellophane) until they covered the plate.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA and genomic DNA were extracted as described previously (56). Identification of genomic regions flanked a NeoR cassette sequence was performed using fusion primer and nested integrated-PCR method, as described previously (21).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated from two fungal strains, DK80 and Δsgf73, infected with CHV1-Δp69, as described by EusebioCope and Suzuki (56). Small RNA cDNA library construction and sequencing were performed by Macrogen Japan using the Illumina TruSeq Small RNA Library Preparation Kit and the HiSeq 2000 system (50-bp single-end reads).…”
Section: Methodsmentioning
confidence: 99%